Promoting Financial and Cultural Citizenship Literacy as Multiliteracy in Tourism Village - Arbarini, Mintarsih; Suminar, Tri; Desmawati, Liliek (Universitas Negeri Semarang, 2021)
Literacy skills provide opportunities to build society to face the global changes. This study aims to promoting the community members of the tourist village according to financial and cultural citizenship literacy as a part of multiliteracy in tourism village. This research applied descriptive qualitative approach. The subjects are 10 villagers in Jojogan Village, Wonosobo Regency. The method of data collecting use interview, observation, and documentation. Data analysis begins during the data collection process, performs data reduction, data presentation, and ends with drawing conclusions and verification. The findings describe promoting financial and cultural citizenship literacy as multiliteracy in Tourism Village is carried out in the community to have a financial and cultural literacy in their daily lives as a part of tourism village community. This activity promotes literacy cultur e by adjusting their free time because the learning schedule was coming from the community member's needs. With this condition, the manager and facilitator continuously try to adjust the conditions of the community members. These literacy learning activities include reading, writing, numerating, speaking, and listening. The benefit of this research is to provide an explanation that financial and cultural citizenship literacy as a part of multiliteracy in tourism village must be done.